Seasonal population dynamics of four species of chewing lice (Phthiraptera: Menoponidae, Philopteridae) on feral pigeons (Aves: Columbiformes: Columbidae). Issue 6 (20th January 2015) - Galloway, Terry D.; Lamb, Robert J.
Abstract: Seasonal dynamics of louse (Phthiraptera) populations on feral pigeons, Columba livia Gmelin (Aves: Columbiformes: Columbidae) were investigated from 2003 to 2012 in southern Manitoba, Canada. Pigeons were infested with: Philopteridae – Campanulotes compar (Burmeister), Columbicola columbae (Linnaeus), and Coloceras tovornikae Tendeiro; Menoponidae – Hohorstiella lata (Piaget). We consider the hypothesis that four species living on the same host show similar seasonal dynamics, coordinated by the life history of the host. Adults of both sexes and nymphs of all four species were present on pigeons throughout the year, consistent with continuous feeding and reproduction. Campanulotes compar and C. columbae populations were low in spring and peaked in September, with C. columbae showing greater seasonal changes for all population parameters. Coloceras tovornikae showed two annual peaks in abundance in spring and late summer, and H. lata was most abundant in the cold months of the year. Over 10 years, the four species showed distinct seasonal dynamics, although they live on the same birds. Seasonal patterns provided no evidence that louse reproduction or abundance is coordinated by the long breeding and moulting seasons of the host.